THE STATE OF WATER RESOURCES AND WATER SUPPLY SYSTEMS IN THE CONTEXT OF GLOBAL CHALLENGES AND UZBEKISTAN’S NATIONAL STRATEGY - SHARIPOVA , GUZAL; ABDUJABBOROVA , NOZANAINKHON (INTERNATIONAL CONFERENCE ON MODERN RESEARCH AND SCIENTIFIC INNOVATION, 2026)
Water security in the XXI st century has transformed from an environmental issue into a key factor in global macroeconomic stability, directly affecting national security. Today, access to clean drinking water is fundamental to life, supporting food systems, economic growth, and the health of nations and ecosystems. However, anthropogenic pressures and climate change have led to a crisis in the global water sector. In particular, in the Republic of Uzbekistan, located in an arid zone (an area dominated by deserts and semi-deserts, author’s note) with limited water resources, issues of rational water use and modernisation of water supply infrastructure are of existential importance.